Creating a lean culture : tools to sustain lean conversions - Mann, David, 1947- (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
"The new edition of this Shingo Prize-winning bestseller explains how to implement a Lean transformation that works by developing a culture that builds success from the top down and the bottom up at the same time. This edition provides expanded coverage of executive responsibilities, 20 new case studies, and new examples from the healthcare and process industries. A must-read for any leader undergoing or considering a Lean transformation, this edition also includes expanded coverage of Lean management applications in complex cross functional value stream process improvement projects"--
Includes bibliographical references (page 349) and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Organizational effectiveness; Industrial efficiency; Organizational change; Corporate culture; Electronic books